Pengembangan Media Powerpoint Interaktif pada Pembelajaran IPAS Materi Ekosistem Kelas V SDI Mu’tashim Billah Pontianak Selatan - Ningsih, Yulistiani; Kartono, Kartono; Salimi, Asmayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This research aims to determine the process of developing interactive Powerpoint media in learning science and science material on ecosystems for class V SDI Mu’tashim Billah South Pontianak. The research method used is research and development (RnD) using the ADDIE model. The data sources for this research were a class V teacher, 17 student and two expert validators, namely media experts and material experts. Data collection techniques in this research were interviews and questionnaires. The research results show that the development of interactive Powerpoint media goes through three research steps, namely analysis, design and development. At the analysis stage the research carrid out interviews and distributed needs questionnaires. The research results show that the development of interactive Powerpoint media goes through three research steps, namely analysis, design and development. At the analysis stage the research carried out interviews and distributed needs questionnaires. The steps taken at the design stage are determining learning outcomes and designing Powerpoint media. Based on the result of the data obtained at the development stage, the feasibility of interactive Powerpoint products reseived “very valid” criteria from expert validators, namely the media aspect received an average value of 37,5. The material aspect received an average value of 3,5 and from the results of students’ responses to the use of interactive Powerpoint, they obtained “very good” criteria, namely the response to small group trials obtained an average score of 37,6 and large group trials obtained a score of 38,1.